2019
DOI: 10.5005/jp-journals-10005-1579
|View full text |Cite
|
Sign up to set email alerts
|

Is Resin Infiltration a Microinvasive Approach to White Lesions of Calcified Tooth Structures?: A Systemic Review

Abstract: Aim The treatment of white lesions should aim at arresting the lesion progression of carious lesions and improving the esthetics by diminishing the opacity of the developmental disturbances of a tooth. The objective of this review was to present the scientific basis, the principles of resin infiltration and to discuss its inherent clinical applications. Data sources Data were identified by PubMed searches. Papers published in English between 2010 and 2015 were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…Removal of the biofilm, such as by toothbrushing and interdental flossing, together with dietary control, focused on prevention rather than halting carious lesions [ 8 , 9 ]. Remineralisation of the enamel lesion with fluoride and casein phosphopeptide amorphous calcium phosphate (CPP-ACP) is promising [ 7 , 10 , 11 ], but it lacks validity without good compliance [ 7 , 12 ]. Consequently, micro-invasive treatments have been developed as alternatives since they are less dependent upon patient compliance and are more conservative than invasive treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of the biofilm, such as by toothbrushing and interdental flossing, together with dietary control, focused on prevention rather than halting carious lesions [ 8 , 9 ]. Remineralisation of the enamel lesion with fluoride and casein phosphopeptide amorphous calcium phosphate (CPP-ACP) is promising [ 7 , 10 , 11 ], but it lacks validity without good compliance [ 7 , 12 ]. Consequently, micro-invasive treatments have been developed as alternatives since they are less dependent upon patient compliance and are more conservative than invasive treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the capillary force, resin penetrates into the pores of demineralized enamel and establishes a barrier to impede acid diffusion [ 18 , 19 ]. Thus, micro-porosities are filled, and light scattering of the lesions turns out to be similar to the sound enamel [ 12 ]. At the same time, sealing has been investigated to efficiently arrest lesion progression in vivo and in vitro [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have clearly indicated previously that RI is actually a microinvasive esthetic dental procedure with lab as well as clinical findings backing its authenticity. Merging this microinvasive method with a significant caries remineralization system may offer therapeutic advantages and substantially decrease both long term restorative requirements and expenses, thus completing the idea of minimum intervention dentistry [8].…”
Section: Discussionmentioning
confidence: 99%
“…Lesions have to be limited to enamel and the outer third of dentine. 61,62,63,64,65 It can also camouflage the whitish appearance of hypomineralised enamel on smooth surfaces. 62,64 Similar to sealants, this is also known as a micro-invasive treatment.…”
Section: Resin Infiltrationmentioning
confidence: 99%